Applying social media to environmental education: is it more impactful than traditional media?. Issue 4 (24th June 2020) - Chung, Chi-Hung; Chiu, Dickson K.W.; Ho, Kevin K.W.; Au, Cheuk Hang
Abstract : Purpose: This study aims to explore how social media help promote environmental education and pro-environmental behaviours by analysing how young adults access social media and traditional media to obtain environmental information differently, how environmental ideas are disseminated through social media and how people perceive and realise environmentalism. Design/methodology/approach: This is a qualitative study based on a semi-structured interview with student participants. The questions used in the interview were developed by on the integrated waste reduction model by Nishio and Takeuchi (2005) and the enhanced model proposed by Ho et al. (2019). Findings: The results indicate that young adults agree and accept that living environmentally friendly lifestyles is an important goal. Although they acquire environmental information from social media, they seldom share or interact with those social media posts. This behaviour implies that they are information receivers when dealing with such contents. Originality/value: The finding of this study provides insight for stakeholders on how to promote related knowledge and encourage people to be "greener" more often and construct a friendlier atmosphere for fostering more in-depth environmental discussions on social media.